Enzyme Immobilization on to Magnetic Microparticles Functionalized with Polydopamine - Wang, Xinyue (Université d'Ottawa | University of Ottawa, 2025)
Enzymes are highly efficient biocatalysts. However, their industrial applications have been in many scenarios limited due to their narrow pH and temperature optima, poor recoverability, reusability, and stability. Immobilizing enzymes on appropriate carriers has been proven to be an effective approach addressing these issues. This thesis introduces an innovative approach utilizing polydopamine-functionalized microparticles as carriers for enzyme immobilization. The immobilization of three enzymes of vastly different molecular weights and structures, including alcalase and two lipases, was studied by experimental investigations and bioinformatic analysis. The microparticles were functionalized by coating with polydopamine (PDA), which were then grafted with either glutaraldehyde (GA) or polyethyleneimine (PEI) as the spacer for immobilization of enzymes. Various parameters, including functionalization conditions GA concentrations, enzyme properties and concentration, spacer structure and concentration, as well as immobilization conditions, were systematically investigated to assess their effects on the loading density, enzymatic activity, and specific enzymatic activity. The results revealed significant improvements in temperature and pH stability, broadening of pH and temperature optima, and improved recoverability and reusability with the immobilized alcalase maintaining 72.3% of its relative activity after 10 consecutive uses. The immobilization of the two lipases were studied using either GA or PEI as the spacer. Among various PEI molecular weights tested (600 Da, 1800 Da, and 10000 Da), PEI with a molecular weight of 600 Da provided the most effective immobilization of enzymatic proteins, while PEI with 1800 Da maintained the highest specific enzyme activities and resulted in the highest enzymatic activity per unit mass of immobilized enzymes. Optimal immobilization conditions were identified as a lipase concentration of 4.25 mg/ml, pH 6, immobilization time of 5 hours, and temperature of 10°C. The immobilized lipase demonstrated a broader optimal pH range and improved thermal stability, retaining 50% of its activity after 10 cycles of enzymatic reactions, indicating excellent reusability and stability.
Keywords: Enzyme immobilization; PDA modification; magnetic carrier; alcalase; lipase